The Effect of Remuneration, Work Environment, and Employee Welfare Programs on Work Productivity at PT Petrokimia Kayaku - Rina Wijayanti; Gancar Candra Premananto (Green Publisher Indonesia, 2022)
The purpose of this study was to determine the effect of remuneration on work productivity, the effect of the work environment on work productivity, the effect of employee welfare programs on work productivity, the effect of the three factors mentioned above on work productivity and to find out which variables have the most influence on work productivity. The research approach used in this study is a quantitative approach. In this study, data and information were obtained from respondents using a questionnaire. Types of data sources used in this study, namely quantitative data. The data analysis technique in this study used basic statistics, namely descriptive analysis. Based on the results of the calculation of the t-test table (table 18) it can be seen that the confidence level is 0.05 and the t-table value is 2.05, the calculated remuneration value is 8.042 and the probability value of t-value is 0.000 means that Ho is rejected and Ha is accepted, then this means that remuneration has a significant effect on employee productivity. From the results of the analysis, it is known that the remuneration variable consisting of elements of work standards, working time, number of products, product quality and increasing work ability, each has a significant effect on work productivity variables.